Understanding crowd management in sports events: a preliminary study/ Lina Munirah Kamarudin, Nur Azyan Raihan Abd Aziza and Asmahany Ramely - Kamarudin, Lina Munirah; Abd Aziz, Nur Azyan Raihan; Ramely, Asmahany (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Sport tourism events have increased in popularity due to their unique characteristics, and therefore it needs effective and successful planning because they would increase the total crowd size. However, a peaceful event could devolve into a disaster if effective crowd management is not implemented, and the failure in crowd management only exposes the attendees to high risk and accidents. Thus, a compelling crowd management belief is crucial for the safety and enjoyment of the people visiting the event. In relating to this concern, this preliminary study aims to understand crowd management strategy in sports events, specifically regarding the factors that lead to the crowd in sports events, crowd impacts on sports events, and crowd management strategies used by the event organizer. This study adopted a qualitative research method that focuses on semi-structured interviews with two event managers who have more than five years of experience in crowd management of sports events by using this sampling technique. This study found that management and attractions as the two primary factors that led to the crowd in the sports events. The crowd also had both positive and negative impacts on the sports events. Besides, forecasting and enhancing the job skills among the event organisers are the strategies that can be adopted in managing the crowd. The findings of this study are significant to be used as a guide for other event organisers or spectators at sporting events who aim to minimise risk and crowding at the event venue.